PELATIHAN PEMBUATAN ALAT PENJERNIHAN AIR PADA MASYARAKAT KECAMATAN SEBAWI KABUPATEN SAMBAS - Dedeh Kurniasih; Raudhatul Fadhilah (Universitas Muhammadiyah Pontianak, 2016)
The problematic issue of water shortages is always happens in dry season because of rainwater absorption in the peat soil which dominates most of the Borneo region especially Rantau Panjang subdistrict. The river water around peatlands area has typical smell, colour, and taste. Peat water has to be processed rightly before it is used to fulfill domestic needs. Therefore, there should be an effort to process the peat water appropriately through counseling and training in producing simple water purifier which is easy to operate. This dedication on the training in producing water purifier was conducted at Sebawi district in Sambas regency. There were 24 residents of Rantau Panjang subdistricts attended this training. The training began with the counseling in how to produce water purifier. The counseling aimed at transferring knowledge of the importance of clean water for the residents of Rantau Panjang subdistrict. The next activity was the training in producing water purifiers from simply and locally available materials. In this activity, the participants were given opportunity to practice producing water purifier. The participants were so enthusiastic in this training. Keywords: training, producing, water purifier equipment.